KAPABILITAS PEGAWAI BALAI BESAR PENGAWAS OBAT DAN MAKANAN (BBPOM) DALAM MELAKUKAN PENGAWASAN OBAT DAN MAKANAN DI PEKANBARU - Maygita, Indri; Sadad, Abdul (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
This study aims to determine: 1) the ability of the staff of the Center for Drug and Food Control (Bbpom) in conducting drug and food control in Pekanbaru. 2) factors that hinder the ability of the staff of the Center for Drug and Food Control (Bbpom) in conducting drug and food control in Pekanbaru. This study uses the Capability theory, Moenir (2008) explains that the capabilities that must be possessed by employees are technical abilities, human abilities and conceptual abilities. The research method in this study is a qualitative method with data collection through interviews, observation and documentation. The informants in this study were employees of the pharmaceutical supervisory division and the first supervisor, general administration and employees of the analysis section of the BBPOM Drug Investigator and Drug Investigator, drug stores and the public. Data analysis used the Interactive Analysis Model technique. The results showed that the staff of the Center for Drug and Food Control (BBPOM) in carrying out the supervision were capable. However, there are inhibiting factors in employees carrying out supervision, namely the lack of facilities and infrastructure and the lack of human resources as well as the conceptual ability factor, namely the covid-19 pandemic.Â Keywords: Capability, Performance, Supervision, Human Resources, Employees.